Conceptualisation of intellectual capital in analysts' narratives: a performative view. Issue 3 (19th March 2018) - Abhayawansa, Subhash; Aleksanyan, Mark; Cuganesan, Suresh
Abstract : Purpose: The purpose of this paper is to test the performativity of intellectual capital (IC) from the perspective of sell-side analysts, a type of actor who consumes and creates IC information and in whose practice IC information plays a significant role. Design/methodology/approach: The empirical component of the study comprises a narrative analysis of the text of a large corpus of sell-side analysts' initiation coverage reports. The authors adopt Mouritsen's (2006) performative and ostensive conceptualisations of IC as the theoretical framework. Findings: The authors find that the identities and properties of IC elements are variable, dynamic and transformative. The relevance of IC elements in the eyes of analysts is conditional on the context, temporally contingent and bestowed indirectly. IC elements are attributed to firm value both directly, in a linear manner, and indirectly, via various non-linear interrelationships established with other IC elements, tangible capital and financial capital. Research limitations/implications: This study challenges the conventional IC research paradigm and contributes towards a performativity-inspired conceptualisation of IC and a resultant situated model of IC in place of a predictive model. Originality/value: This is the first study to apply a performative lens to study IC identities, roles and relationships from the perspective of a field of practice that is external to the organisation where IC is hosted. Examining IC from analysts' perspective is important because not only can it provide an alternative perspective of IC, it also enables an understanding of analysts' field of practice.